INDUSTRI TPT INDONESIA DALAM ACFTA : Siapa Juragan di Pasar Domestik? - Rahman, Agus Rubianto (Jurnal Penelitian Politik, 2025)
ACFTA was in force since January 2010 in six ASEAN countries and otherfour ASEAN countries in 2015 Implementation of thefree trade area between China and ASEAN countries is possible and becomes political and economic reality It is historical achievement in their relations in which prior to their relations are colored by tremendous crisis As free trade regions ACFTA banding almost 1 9 billion peoples represented as the biggest free trade area in the world From the beginning ACFTA is further revitalization of AFTA that ASEAN countries prefer to be integrated by external actor in which China is more acceptable than Japan or South Korea ACFTA will show opportunities andproblems for all economic actors around the region especially for Indonesia te aile and textile product This makes Indonesian market as second market after China s market Indonesia still does not give the high priority in export yet towardACFT4 but its percentage consistently tended to increased For import Indonesia also increased thisfrom ACFTA countries Based on this national grasp Indonesian textiles and textile products industry arefacing difficult periods especially expansion of China textile and textile product into hxlo nesian domestic market Fortunately Indonesian textile and textile products have received the world heritage in which this emerged as new energyfor revitalization ofIndonesia textile and textile products in strengthening their competitive advantage and market shares in both domestic and international market Now and then Batik starts to be the most outstanding Indonesian icon